The Implementation of Computational Thinking on Mathematics Learning Research: A Systematic Literature Review - Ahmad Mukhibin; Dadang Juandi (Program Studi Tadris Matematika IAIN Salatiga, 2023)
The aim of this study is to describe the implementation of computational thinking research results on mathematics learning in Indonesia. The method used in this study is a systematic literature review (SLR) by using PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) protocol. The sample consists of 25 results of computational thinking research on mathematics learning, the sample is journal articles and proceedings published in 2019-2023. The description of this research will be reviewed based on the year of research, the level of education, research location, and research methods used. The results of the study show that (1) computational thinking research on mathematics learning has increased every year where 2022 become the year with the most number of publications, there are 15 articles, (2) 32% (8 articles) of computational thinking research on mathematics learning is conducted at the university level, (3) East Java is the province with the most research on computational thinking on mathematics learning, with 7 studies, (4) quantitative method is the method most frequently used in computational thinking research on mathematics learning in Indonesia, there are 12 studies that used quantitative method, and (5) students are able to perform abstraction and algorithm processes. However, they still have difficulty in performing the decomposition and pattern recognition processes.